2003
DOI: 10.1038/sj.bjc.6601196
|View full text |Cite
|
Sign up to set email alerts
|

HPV infection and number of lifetime sexual partners are strong predictors for ‘natural’ regression of CIN 2 and 3

Abstract: The aim of this paper was to evaluate the factors that predict regression of untreated CIN 2 and 3. A total of 93 patients with colposcopic persistent CIN 2 and 3 lesions after biopsy were followed for 6 months. Human papillomavirus (HPV) types were determined by polymerase chain reaction at enrolment. We analysed the biologic and demographic predictors of natural regression using univariate and multivariate methods. The overall regression rate was 52% (48 out of 93), including 58% (22 out of 38) of CIN 2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 31 publications
(32 reference statements)
1
30
1
4
Order By: Relevance
“…This confirms our study (OR-5.10, p -0.042), and many other published works on this subject [13,16,17,[36][37][38]. Moscicki says that a large number of sexual partners is an independent risk factor for HPV infection and cervical cancer.…”
Section: Discussionsupporting
confidence: 81%
“…This confirms our study (OR-5.10, p -0.042), and many other published works on this subject [13,16,17,[36][37][38]. Moscicki says that a large number of sexual partners is an independent risk factor for HPV infection and cervical cancer.…”
Section: Discussionsupporting
confidence: 81%
“…O incremento observado no diagnóstico de lesões pré-neoplásicas cervicais em adolescentes explica-se, em grande parte, pela elevada prevalência da infecção pelo HPV nessa faixa etária 16 . O aumento da infecção por esse vírus, assim como a presença de outras DSTs, relaciona-se, possivelmente, à mudança no comportamento sexual desse grupo, em especial ao aumento no número de parceiros sexuais e à precocidade da primeira relação sexual 27,28 . O desenvolvimento de lesões intra-epiteliais cervicais parece ser diretamente proporcional ao número de parceiros referido pelas adolescentes 29 , possivelmente devido ao aumento da probabilidade de infecção pelo HPV conseqüente à maior exposição sexual 12,14 .…”
Section: Discussionunclassified
“…At enrolment into the study, HPV infection was detected in 84% (78 out of 93) women and most patients had HPV types that were considered high risk for progressing to cancer. Chan et al 78 reported that in multivariate analysis, HPV status and the number of sexual partners remained as significant independent predictors of regression of untreated CIN2 and CIN3.…”
Section: Hpv Infectionmentioning
confidence: 99%
“…In 2003 Chan et al 78 reported on a study that evaluated factors that predict regression of untreated CIN2 and CIN3. A cohort of 93 women with untreated CIN2 or CIN3, from a prospective, double-blinded, randomised, placebo-controlled trial of -carotene, were prospectively analysed.…”
Section: Hpv Infectionmentioning
confidence: 99%